Insidensi Prehipertensi Pada Populasi Laki-Laki Usia 35-65 Tahun Di Puskesmas Nabarua Kabupaten Nabire Propinsi Papua - Marthen Todeng; Masriadi Masriadi (Universitas Muhammadiyah Manado, 2020)
The occurrence of an epidemiological transition that is parallel to the demographic transition and technological transition in Indonesia today has resulted in a change in disease patterns from infectious diseases to non-communicable diseases (NCDs) including degenerative diseases and man-made diseases which are the main factors in morbidity and mortality problems. This study aims to determine the incidence of prehypertension in the population aged 35 - 65 years at the Nabarua Health Center, Nabire district, Papua province in 2018. This research was carried out at the Nabarua Community Health Center, Nabire Regency, Papua Province in 2018. With a sample size of 60 respondents. Sampling was carried out purposively. The data was analyzed using statistical analysis via the Chi.Square test. The results of the study showed that the statistical test results obtained a calculated X² value (7.828) > X² table (3.841) and a p value (0.050) < 0.05, in this case there is a significant relationship between obesity and prehypertension in men aged 35-65 years. The statistical test results showed that the calculated X² value (9.141) > X² table (3.841) and the p value (0.027) < 0.05, in this case there is a relationship between alcohol and prehypertension in men aged 35-65 years. get the calculated X² value (8.385) > X² table (3.841) and p value (0.039) < 0.05, in this case there is a significant relationship between stress and prehypertension in men aged 35-65 years